Peripartum cardiomyopathy: case report - Macas, Andrius; Rimaitis, Kęstutis; Bakšytė, Giedrė; Šilinskytė, Laura (Acta medica Lituanica, 2012)
Peripartum cardiomyopathy is an unusual and uncommon form of dilat ed cardiomyopathy that is often fatal to young women, the cause of which is unknown. Diagnostics is difficult and requires vigilance. The treatment does not differ from other forms of heart failure. Fetal outcome, however, is quite good. Maternal outcomes depend on 2–6 months recovery of the left ventricular function. We describe a previously asymptomatic patient who presented with pulmonary edema one day after caesarean section. In this case the solution was favorable to the patient. Complete recovery of the left ventricular function happened earlier than indicated in litera ture.